Chromium as a severe anthropogenic geochemical anomaly in river sediments near a tannery outfall: spatial attenuation, source apportionment and ecological risk screening - Rahat Khan; Shuvashish Das Shuvo; Md. Samium Basir; Md. Abu Bakar Siddique; Javed Mallick; Hoang Thi Hang; Md. Harunor Rashid Khan; Saad Aldawood; Dhiman Kumer Roy; Narottam Saha (Environmental Geochemistry and Health, 2026)
Abstract Relocating a polluting industry can transfer contamination to a new receiving water body rather than eliminate it, yet the resulting sediment footprint is rarely resolved beyond surface contamination. This study quantified the spatial and depth-resolved sediment footprint of relocated tannery discharge in the Dhaleshwari River, Bangladesh, and distinguished anthropogenic from geogenic elemental signatures. Sixty sediment samples from 18 sites were analysed for 15 elements by neutron activation analysis. Sites were evaluated individually and within four spatial zones (discharge, opposite riverbank, upstream, and downstream) using non-parametric statistics, sediment-quality indices, and Positive Matrix Factorisation (PMF). Chromium was the dominant anomaly, with concentrations at the discharge point reaching ~260 times the average crustal value (mean: 24,514 ± 16,058 µg/g), declining significantly with distance from the outfall and differing among zones. Depth profiles showed no significant vertical trend across the full sediment cores, but significant near-surface enrichment occurred in the near-field cores, consistent with episodic, source-proximal deposition. Half of all samples exceeded the chromium Effects Range Median threshold. Source apportionment attributed only 15.5% of elemental variance to anthropogenic, chromium-dominated inputs, compared with 65.5% to natural weathering and 19.0% to mixed natural-industrial signatures. Thus, a comparatively small anthropogenic contribution governs the sediment’s principal screening-level ecological concern. This pattern is consistent with particle-reactive Cr being rapidly retained near its release point, producing a sharply confined hotspot rather than basin-wide dispersion. Because risk estimates are based on total Cr rather than speciation or bioavailability, they do not demonstrate biological toxicity. The findings support prioritising targeted interventions at the discharge zone over basin-wide remediation for managing industrial river contamination in comparable settings.